The formation of dinuclear trichloro‑bridged and mononuclear ruthenium complexes from the reactions of dichlorotris(p‑tolylphosphine)ruthenium(II) with diazabutadiene ligands - Tay, Meng Guan; Chia, Ying Ying; Hui, Suzie Chin Kuan; Pan, Tze Pei (Springer Nature, 2019)
Ru(II) complexes with diazabutadiene (R-DAB) ligands have been prepared. The reaction of RuCl3·nH2O with P(p-tolyl)3 gave a [RuCl2{P(p-tolyl)3}] precursor, whose reactions with R-DAB in toluene gave dinuclear trichloro-bridged Ru(II) complexes [Ru2Cl3(P(p-tolyl)3)2(R-DAB)2](BF4) which have been characterized by spectroscopic methods. In addition, one of the complexes was characterized using X-ray crystallography. Meanwhile, two mononuclear Ru(II) complexes [RuCl2(P(p-tolyl)3)2(R-DAB)] were obtained from the reactions of the [RuCl2{P(p-tolyl)3}] precursor with R-DAB ligands in THF. The two trans-mononuclear complexes were characterized by X-ray crystallography and solid-state 31P NMR. A temperature-dependent 31P NMR study was carried out to monitor the formation of dinuclear and mononuclear complexes.